Pemolisian Kolaboratif dalam Penanganan Konflik Sosial: Studi Kasus Konflik Sara di Desa Mareje, Lombok Barat - Donny Bayuanggoro (Jurnal Syntax Admiration, 2024)
This study discusses the application of collaborative policing in handling ethnic, religious, racial, and intergroup (SARA)-based social conflicts with a case study of conflict in Mareje Village, West Lombok, NTB, in 2021. Focusing on the qualitative method of case studies, this study analyzes the dynamics of interactions between the police, the community, and other stakeholders in handling conflicts. The results show that collaborative policing through cross-sector involvement is effective in reducing tensions and supporting post-conflict recovery. However, challenges in communication and synergy between parties are still obstacles in the implementation of this collaborative strategy. This study recommends increased multi-sector engagement and cross-sector collaboration to improve effectiveness in handling future SARA conflicts.